Obstetric claims in Finland 2012-2022-A nationwide patient insurance registry study - Lojander, Jaana (Wiley, 2025)
Introduction: Maternal and infant mortality rates in Finland are among the lowest in the world, yet preventable obstetric injuries occur every year. The aim of this study was to describe obstetric claims, their compensation rates, and temporal trends of claims reported to the Patient Insurance Centre.
Material and methods: A nationwide, register-based study was conducted. Data consisted of obstetric claims reported to the Patient Insurance Centre between 2012 and 2022. Data analyzed included the year of injury, compensation criteria, maternal age, birth hospital, delivery method, reported causes of injury, and maternal or neonatal injury. The data were analyzed with descriptive statistics and logistic regression models.
Results: A total of n = 849 obstetric claims were filed during the study period, of which n = 224 (26.4%) received compensation. The rate of claims was 0.15%, and the rate of compensation was 0.04% in relation to the total volume of births during the period. Substandard care was the most common (97.3%) criterion for compensation. There was a curvilinear increase in the claims rate and a linear increase in compensation rates from 2013 to 2019. More claims were filed and compensated for cesarean and vacuum-assisted deliveries than for unassisted vaginal deliveries. Delayed delivery (18.7%) and surgical technique failure (10.9%) were the most reported causes of injuries. Retained surgical bodies were the induced cause of injury with the highest rate of compensated claims (86.7%). The most common maternal injury was infection (17.9%) and pain (11.7%). Among neonatal injuries, severe (19.2%) and mild asphyxia (16.6%) were the most frequent. Burn injuries (93.3%) and fetal or neonatal death (60.5%) had the highest rate of compensated claims.
Conclusions: The study provided new information on substandard care and injuries in obstetric care in Finland. An increasing trend in claims and compensation rates was found. Identifying contributors to substandard care that lead to fetal asphyxia is important for improving obstetric safety. Further analysis of the association of claims and compensation rates with operative deliveries is needed to determine their causality. Frequent review of obstetric claims would be useful in providing more recent data on substandard care and preventable injuries.